البروتين الارتكاسي C عالي الحساسية في احتشاء العضلة القلبية الحاد - رضوان, عبد الناصر; خياط, محمد عماد; الرجب, معاذ محمد (Latakia University Journal -Medical Sciences Series, 2019)
أجريت هذه الدراسة لإثبات دور الآليات الالتهابية في تكون العصيدة بالإضافة لدورها في جعل الآفات العصيدية قابلة للتمزق أو الأذية . تناولت الدراسة 70 مريضاً مصاباً باحتشاء عضلة قلبية حاد مع ارتفاع وصلة ST راجعوا مشفى الأسد الجامعي باللاذقية، (50 مريضاً خلال 6 ساعات، و 20 مريضاً ≥ 6 ساعات ولكن ˃ 48 ساعة من بدء الاحتشاء). تم قياس الـCRP بالطريقة عالية الحساسية (hs-CRP) عند هؤلاء المرضى، كما تم قياسه أيضاً في 20 مريضاً مصاباً بخناق صدر وفي 10 أشخاص أصحاء. المستويات المصلية لـhs-CRP كانت أعلى بشكل واضح في المرضى الذين بدأ الاحتشاء عندهم منذ أقل من 6 ساعات من أولئك الذين عندهم خناق صدر [( 2.84 ± 1.85 مغ/ل) مقابل ( 1.32 ± 0.7 مغ/ل)] وأعلى أيضاً من الأشخاص الأصحاء [( 2.84 ± 1.85 مغ/ل ) مقابل ( 0.94 ± 0.4 مغ/ل )]. لم تكن هناك اختلافات واضحة في المستويات المصلية لـhs-CRP في مرضى الاحتشاء مع بدء ≤ 3 ساعات من أولئك الذين بدأ الاحتشاء عندهم منذ < 3 ساعات لكن > 6 ساعات [(2.83 ± 1.9 مغ/ل) مقابل (2.85 ± 1.84 مغ/ل)]. وكانت المستويات المصلية لـhs-CRP أعلى بشكل واضح في المرضى الذين بدأ الاحتشاء عندهم منذ ≥ 6 ساعات من أولئك الذين بدء عندهم منذ ˃ 6 ساعات[(23.23 ± 12.9 مغ/ل) مقابل (2.84 ± 1.85 مغ/ل)]. والنتيجة: أن العملية الالتهابية أثبتت كواحدة من الآليات المتسببة ببدء التصلب العصيدي ومن ثم حدوث تمزق للويحات العصيدية . The aim of this study is to establish the important role of inflammatory processes in atherogenesis, as well as to the vulnerability of an atherosclerotic lesion to rupture or erosion. The sample consists of 70 patients with ST-segment elevation AMI at the University Al-Assad Hospital in Lattakia (50 patients within 6 h, and 20 patients ≥6 h but <48h after the onset of AMI).CRP was measured by high-sensitivity CRP assay (hs-CRP) in those patients. Serum levels of hs-CRP were also measured in 20 patients with unstable angina and in 10 healthy control subjects. The serum level of hs-CRP was significantly higher in patients with an onset of AMI <6h than in patients with angina pectoris (2.84 ±1.85 mg/L vs 1.32 ±0.7 mg/L [mean ±SD]) and in healthy subjects (2.84 ±1.85 mg/L vs 0.94 ±0.4 mg/L). There were no significant differences in serum levels of hs-CRP in patients with an onset of AMI ≤3h than in those patients with an onset of AMI >3h but <h (2.83 ±1.9 mg/L vs 2.85 ±1.84 mg/L). The serum level of hs-CRP was significantly higher in patients with an onset ≥6h than in patients with an onset <6h (23.23 ±12.9 mg/L vs 2.84 ±1.85 mg/L). Conclusion: The inflammatory process has been proved to be one of the mechanisms that cause atherosclerosis and posteriorty is followed by an atherosclerotic plaque rupture.